Forensic facial comparison in South Africa: State of the science. (June 2018) - Steyn, M.; Pretorius, M.; Briers, N.; Bacci, N.; Johnson, A.; Houlton, T.M.R.
Highlights: Forensic facial comparison is frequently used in South Africa and worldwide. Here we outline the scope of practice and training in South Africa. We propose new levels for assessment of agreement. The reliability of facial comparisons should be addressed in future research. Abstract: Forensic facial comparison (FFC) is a scientific technique used to link suspects to a crime scene based on the analysis of photos or video recordings from that scene. While basic guidelines on practice and training are provided by the Facial Identification Scientific Working Group, details of how these are applied across the world are scarce. FFC is frequently used in South Africa, with more than 700 comparisons conducted in the last two years alone. In this paper the standards of practice are outlined, with new proposed levels of agreement/conclusions. We outline three levels of training that were established, with training in facial anatomy, terminology, principles of image comparison, image science, facial recognition and computer skills being aimed at developing general competency. Training in generating court charts and understanding court case proceedings are being specifically developed for the South African context. Various shortcomings still exist, specifically with regard to knowledge of the reliability of the technique. These need to be addressed in future research.